Math, asked by Aditi466, 10 months ago

Prove that √1 + sin triangle ÷ 1 - sin triangle = sec Triangle + tan Triangle ​

Answers

Answered by Anonymous
11

{ \bf{ \underline{ \blue{ \underline{ \blue{ Given}}}}  :  - }}

 \bf \implies  \sqrt{ \dfrac{1 +  \sin( \triangle) }{1 -  \sin( \triangle) }}  =  \sec( \triangle)  +  \tan( \triangle)

{ \bf{ \underline{ \blue{ \underline{ \blue{ To- Prove }}}}  :  - }}

 \bf \implies  \sqrt{ \dfrac{1 +  \sin( \triangle) }{1 -  \sin( \triangle) }}  =  \sec( \triangle)  +  \tan( \triangle)

{ \bf{ \underline{ \blue{ \underline{ \blue{ Solution }}}}  :  - }}

L.H.S

 \bf  \:  \:  =  \sqrt{ \dfrac{1 +  \sin( \triangle) }{1 -  \sin( \triangle) }}

( Rationalization of denominator )

 \bf  \:  \:  =  \sqrt{ \dfrac{1 +  \sin( \triangle) }{1 -  \sin( \triangle) } \times  \dfrac{1 +  \sin( \triangle) }{1 +  \sin( \triangle)}}

 \bf  \:  \:  =  \sqrt{ \dfrac{ \{1 +  \sin( \triangle) \}^{2} }{ \{1 -  \sin( \triangle) \} \{1 +  \sin( \triangle)\} }}

 \bf  \:  \:  =  \sqrt{ \dfrac{\{1 +  \sin( \triangle) \}^{2} }{ {(1)}^{2}  -  \sin^{2} ( \triangle)}}

 \bf  \:  \:  =  \sqrt{ \dfrac{\{1 +  \sin( \triangle) \}^{2}}{1 -  \sin^{2} ( \triangle)}}

 \bf  \:  \:  =  \sqrt{ \dfrac{\{1 +  \sin( \triangle) \}^{2}}{\cos^{2} ( \triangle)}}

 \bf  \:  \:  =  \dfrac{1 +  \sin( \triangle) }{\cos ( \triangle)}

 \bf  \:  \:  =  \dfrac{1}{\cos ( \triangle)} +  \dfrac{\sin( \triangle) }{\cos ( \triangle)}

 \bf  \:  \:  =   \sec ( \triangle)+   \tan( \triangle)

= R.H.S

L.H.S = R.H.S

\small{\underline{\sf{\blue{Hence-}}}}

( Proved)

Answered by pranavraswan
0

answer : R.H.S

MARK me as BRAINLIEST and I will follow you and like your answers

Similar questions